Bulk-phase and interface stability strategies of manganese oxide cathodes for aqueous Zn-MnOx batteries - Yang, Gaoqi; Wan, Houzhao (Frontiers in Chemistry, 2022)
The cyclic stability of the MnOx cathodes for rechargeable zinc ion batteries have substantial obstacles due to Mn3+ disproportionation produces Mn2+ caused by Jahn Teller lattice distortion effect in the process of Zn2+ inter/deintercalation. This mini review summarized bulk-phase and interface stability strategies of manganese oxide cathodes for aqueous Zn-MnOx batteries from the regulation of bulk electronic state of manganese oxide improves its structural stability and the formation of beneficial SEI layer at the interface of electrolyte. It provides theoretical support for the design of manganese oxide cathode materials for aqueous zinc ion batteries with high stability.